Analysis of the Effect of Inflation on Exports of Non-Oil and Gas Commodities Through the Port of Tanjung Perak Surabaya - Bambang Purwoko (Eduvest - Journal of Universal Studies, 2021)
Export-import activities are based on the condition that no one country or region is truly independent because they need and complement each other. In order to increase the growth of the national economy, it is necessary to encourage non-oil exports. The aim of this study is to analyze the effect of inflation on non-oil and gas commodity exports in 2017-2019. The research conducted by the researcher is a quantitative correlation study by understanding the relationship between variables, in this case the effect of inflation on the export of non-oil and gas commodities through the Tanjung Perak Port of Surabaya in 2017-2019. The population of this study was taken from data from the Annual Report of Bank Indonesia and the Port of Surabaya Harbormaster for the 2017-2019 period. The sample data is from January 2017 to December 2019. This study used documentation in collecting the data. The documentation method is a method of finding data or information related to research variables through notes, literature, documentation, and others. The analysis data in this study is used descriptive statistical, classic assumption tests and simple linear regression tests. The results of the study conclude that inflation has a significant positive effect on exports of non-oil and gas commodities through the Port of Tanjung Perak Surabaya in 2017-2019.